1982
DOI: 10.1207/s15327752jpa4604_8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Depression Among Incarcerated Females

Abstract: The use of the abridged BDI as a depression screening device for a sample of recently incarcerated adult female felons was explored, and the concurrent validity of the instrument was examined. The results indicated that the abridged BDI was a highly reliable measure which substantially and significantly correlated with the MMPI D scale, as well as other MMPI scales. In addition, individuals who tended to score high or depressed on the abridged BDI consistently described themselves on self-concept rating scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Good suggested that an affective disorder may be masked by drug and alcohol use. A similar descriptive study completed at the Iowa Women' s Reformatory in 1982 indicated that the average inmate score indicated mild depression; however, 10% experienced high levels of depression (Scott, Hannum, & Ghrist, 1982).…”
Section: Psychological Well-being In Female Offendersmentioning
confidence: 94%
“…Good suggested that an affective disorder may be masked by drug and alcohol use. A similar descriptive study completed at the Iowa Women' s Reformatory in 1982 indicated that the average inmate score indicated mild depression; however, 10% experienced high levels of depression (Scott, Hannum, & Ghrist, 1982).…”
Section: Psychological Well-being In Female Offendersmentioning
confidence: 94%
“…Study ndings also have supported high rates of mental health problems in population s of jailed women (Jordan, Schlenger, Fairbank, & Caddell, 1996;Novick, Della Penna, Schwartz, Remmlinger, & Lowenstein, 1977;Scott, Hannum, & Ghrist, 1982;Teplin et al, 1996). Over 40% of incarcerated women have some kind of DSM-III psychiatric diagnosis (Washington & Diamond, 1985).…”
Section: Review Of the Literaturementioning
confidence: 96%
“…Although information on the health status of incarcerated women tends to be fragmentary, there is indication of a high incidence of gynecological disorders (Bell et al, 1985), sexually transmitted disease (Resnick & Shaw, 1980), and psychiatric illness, particularly depression (Scott et al, 1982;Turner & Toffler, 1986). In a recent study of women in prison (Ingram-Fogel, 1991), 135 inmates were interviewed during their first week of incarceration; of these, 55 were interviewed again after six months in prison and additional data were collected from chart reviews.…”
Section: Characteristics Of Incarcerated Womenmentioning
confidence: 99%